Equity investment under IAS/IFRS and VAS :A thesis submitted as a requirement for the degree of Bachelor of Finance and Banking /Nguyễn Khánh Linh ; Chu Huy Anh supervisor. - Nguyễn, Khánh Linh.
A thesis submitted as a requirement for the degree of Bachelor of Finance and Banking.